2017
DOI: 10.21897/assensus.1332
|View full text |Cite
|
Sign up to set email alerts
|

Incidencia de las habilidades sociales en el desempeño académico de estudiantes de sexto grado

Abstract: En este trabajo se evaluó la incidencia de las habilidades sociales: empatía, asertividad, trabajo en equipo y autoestima en el desempeño académico de estudiantes de sexto grado. La investigación se enmarca en un enfoque mixto (Creswell, 2009) puesto que en ella se combinan técnicas y métodos de investigación cuantitativos y cualitativos. La muestra la conformaron 155 estudiantes de sexto grado de dos instituciones del municipio de Sincelejo. Los resultados evidencian que el nivel de desarrollo de las habilida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Firstly, as in previous studies [19], we observed a relationship between social skills and academic performance. Other authors [18] have found a relationship between specific social skills, such as empathy and teamwork, and academic performance. However, according to Oyarzún et al [20], the association between these variables remains unclear.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Firstly, as in previous studies [19], we observed a relationship between social skills and academic performance. Other authors [18] have found a relationship between specific social skills, such as empathy and teamwork, and academic performance. However, according to Oyarzún et al [20], the association between these variables remains unclear.…”
Section: Discussionmentioning
confidence: 90%
“…However, the results from previous investigations in this field are difficult to interpret. Some authors [18][19][20] have suggested that a positive association exists between academic performance and social skills such as self-esteem and empathy. However, the level of empathy and assertiveness ranges from good in some studies [18], to moderate-high [3,21] and moderate-low [22] in others.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, they determined that equivalent contextual and cultural traits maintain specific behavioral structures that dynamize its development. Similarly, Contreras et al (2017) studied young people from two educational institutions. They obtained heterogeneous results at the individual and group levels in terms of their development of social skills (such as assertiveness and teamwork).…”
Section: Discussionmentioning
confidence: 99%